2003
DOI: 10.1097/00005537-200311000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Coblation tonsillectomy versus dissection tonsillectomy: Postoperative hemorrhage

Abstract: In the study, coblation tonsillectomy was associated with a lesser incidence of delayed hemorrhage, more significantly in the pediatric population. The new technique using tissue coblation for tonsil dissection offers significant advantages in the postoperative period compared with dissection tonsillectomy with bipolar diathermy hemostasis. Coblation is associated with less postoperative pain and early return to daily activities. Also, there are fewer secondary infections of the tonsil bed and significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 20 publications
4
85
2
3
Order By: Relevance
“…In our study, we found that nearly 86 % of patients were already on oral antibiotics at the time of presentation with secondary haemorrhage. Belloso et al [12] in their study report secondary haemorrhage rate of 2.25 % for coblation tonsillectomy compared to 6.19 % for cold dissection.…”
Section: Discussionmentioning
confidence: 90%
“…In our study, we found that nearly 86 % of patients were already on oral antibiotics at the time of presentation with secondary haemorrhage. Belloso et al [12] in their study report secondary haemorrhage rate of 2.25 % for coblation tonsillectomy compared to 6.19 % for cold dissection.…”
Section: Discussionmentioning
confidence: 90%
“…4 In their study they found that coblation tonsillectomy was associated with a lesser incidence of delayed hemorrhage, significantly in the pediatric population. They found that secondary re-bleed rate with coblation was 2.25% versus 6.19% in the control group.…”
Section: Discussionmentioning
confidence: 95%
“…These findings were in consonance with earlier studies by Belloso and Magdy. 4,7 Most of the studies involving coblation tonsillectomies have focused on adults and adolescents whose clinical data were not applicable for children. The present study sought to find the clinical advantages of coblation if any by assessing clinical outcomes of coblation tonsillectomy compared to cold dissection tonsillectomy especially in children…”
Section: Discussionmentioning
confidence: 99%
“…(2) Tonsillectomy has been practiced for more than 2000 years (Celsus, 30 B.C.). (1,3) Although indications for tonsillectomy have included a large number of conditions over the years, most procedures have traditionally been performed to address infection, either recurrent or chronic. More recently, a trend towards airway obstruction as a common indication for tonsillectomy has emerged because of increasing information about the causes and sequelae of obstructive sleep apnea (OSA).…”
Section: Introductionmentioning
confidence: 99%